2016
DOI: 10.1016/j.msea.2016.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Strain-hardening behavior and microstructure development in polycrystalline as-cast Mg-Zn-Y alloys with LPSO phase subjected to cyclic loading

Abstract: The strain-hardening behavior and microstructural development of polycrystalline as-cast Mg-Zn-Y alloys with various volume fractions of the long-period stacking ordered (LPSO) phase subjected to cyclic loading were experimentally evaluated. For all alloys, cyclic loading tests with a constant strain amplitude of 0.5% for up to 100 cycles showed asymmetric cyclic hardening behavior. That is, the absolute value of the compressive peak stress significantly increased during cyclic loading while the tensile peak s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Original dislocation tangling would hinder further movement of other dislocations. Considering the effects of grain size and dislocations, a recent model indicates that [10][11][12][13][14]35] :…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Original dislocation tangling would hinder further movement of other dislocations. Considering the effects of grain size and dislocations, a recent model indicates that [10][11][12][13][14]35] :…”
Section: Discussionmentioning
confidence: 99%
“…temperature, and strain rate [11][12][13][14] . Jahedi et al [12] reported that strain hardening was strongly related to twinning and texture.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It can be seen that decreasing grain size weakens the strain hardening ability by reducing dislocation density and twinning content. Many studies also reported similar results . However, dislocation annihilation weakened by increasing Al solute atoms and non‐basal slips are easier to activate with the decreasing intensity of basal texture.…”
Section: Discussionmentioning
confidence: 55%
“…For this reason, many researchers have studied the strain hardening behavior in magnesium alloys, while changing various parameters such as grain size, twinning, texture, temperature, strain rate, and second phase . Shiraishi and Mayama reported that strain hardening behavior had some correlations with second phase . Jahedi and McWilliams found strain hardening behavior to be strongly related to twinning and texture .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a gradual increase in YS was found for the tensile side of the cycle in Mg 99.2 Zn 0.2 Y 0.6 alloy. In cast Mg-LPSO alloys, besides the influence of the composition, the effect of compressive pre-loading was studied [25]. Both the compressive pre-loading and the higher LPSO content increased the share of the kinematic hardening to cyclic hardening.…”
Section: Introductionmentioning
confidence: 99%